Chromolaena odorata - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
More commonly known as Laos weed, this plant was introduced to Africa in 1937 as a cover crop and it has now spread throughout West Africa, particularly in deforested areas. From 2 to 4 metres high, it grows quickly almost anywhere, spread by its...